On/off switchable physical stimuli regulate the future direction of adherent cellular fate. Issue 27 (25th June 2021) - Jun, Indong; Han, Hyung-Seop; Lee, Jae Won; Lee, Kyungwoo; Kim, Yu-Chan; Ok, Myoung-Ryul; Seok, Hyun-Kwang; Kim, Young Jun; Song, In-Seok; Shin, Heungsoo; Edwards, James R; Lee, Kuen Yong; et al.
Abstract : A simple method to regulate cell function with anisotropic shape using enzymatically degradable alginate hydrogels offers physical stimuli for reversible cell patterning that allows regulation of the future direction of adherent cellular behaviors. Abstract : The utilization of cell-manipulating techniques reveals information about biological behaviors suited to address a wide range of questions in the field of life sciences. Here, we introduced an on/off switchable physical stimuli technique that offers precise stimuli for reversible cell patterning to allow regulation of the future direction of adherent cellular behavior by leveraging enzymatically degradable alginate hydrogels with defined chemistry and topography. As a proof of concept, targeted muscle cells adherent to TCP exhibited a reshaped structure when the hydrogel-based physical stimuli were applied. This simple tool offers easy manipulation of adherent cells to reshape their morphology and to influence future direction depending on the characteristics of the hydrogel without limitations of time and space. The findings from this study are broadly applicable to investigations into the relationships between cells and physiological extracellular matrix environments as well as has potential to open new horizons for regenerative medicine with manipulated cells.